Using Small-Sided Games or Their Combination with Speed Endurance Training: Which Is More Effective for Improving Aerobic Capacity in Young Amateur League Soccer Players? - Norrahmah, Feni; Zalillah, Shery Iris; Kusuma, I Dewa Made Aryananda Wijaya; Syafii, Imam; Bulqini, Arif; Fajar, Muhammad Kharis; Bharlaman, Muhammad Bagus Firzam (Physical Education Theory and Methodology, 2025)
Objectives. This study aimed to analyze the differences in the effects of Small-Sided Games (SSG) and a combination of Small-Sided Games with Speed Endurance Training (SSG+SET) on the aerobic capacity of young amateur league soccer players, as measured by total distance coverage and VO2max. Materials and methods. A total of 36 young amateur league soccer players were selected as samples and divided into two groups using the matching-group technique. The average sample characteristics were 20.08 ± 0.97 years of age, 170.47 ± 4.77 cm in height, 62.98 ± 5.89 kg in weight, and a body mass index of 20.08 ± 0.97 kg/m². Both groups underwent 12 training sessions over four weeks, with a frequency of three sessions per week. Aerobic capacity was measured using the Yo-Yo Intermittent Recovery Test Level 1 to evaluate total distance coverage and VO2max before and after the intervention. Results. Both training methods had a positive impact on improving aerobic capacity. However, the group undergoing the SSG+SET combination showed significantly greater improvements compared to the SSG-only group (p < 0.05). The SSG+SET group demonstrated a larger increase in total distance coverage and higher VO2max values, reflecting physiological adaptations such as improved oxygen utilization efficiency and cardiovascular function. Conclusions. The findings indicate that the combination of Small-Sided Games and Speed Endurance Training is more effective in enhancing the aerobic capacity of young amateur league soccer players, particularly in terms of total distance coverage and VO2max. This method offers a comprehensive approach to improving physical fitness while simultaneously supporting the development of technical and tactical skills through specific game simulations.